2013
DOI: 10.1177/0046958013513675
|View full text |Cite
|
Sign up to set email alerts
|

The Expansion of Medicaid Coverage under the ACA

Abstract: The expansion of Medicaid coverage under the Affordable Care Act offers the potential for significant increases in health care access, use, and spending for vulnerable nonelderly adults who are uninsured. Using pooled data from the Medical Expenditure Panel Survey, this study estimates the potential effects of Medicaid, controlling for individual and local community characteristics. Our findings project significant gains in health care access and use for uninsured adults who enroll in Medicaid coverage and hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Patients with severe mental disorders, such as schizophrenia or bipolar disorder, had high healthcare costs. 17 , 24 – 26 , 30 , 37 Clemans-Cope et al 17 found the average annual cost per patient with one or more mental disorders to be $11,120 (after summing the separately presented payer costs and out-of-pocket costs), well above the average they found of $9,273 per patient with one or more chronic conditions overall.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Patients with severe mental disorders, such as schizophrenia or bipolar disorder, had high healthcare costs. 17 , 24 – 26 , 30 , 37 Clemans-Cope et al 17 found the average annual cost per patient with one or more mental disorders to be $11,120 (after summing the separately presented payer costs and out-of-pocket costs), well above the average they found of $9,273 per patient with one or more chronic conditions overall.…”
Section: Discussionmentioning
confidence: 93%
“…Of these, 29 original research articles 12 40 met the selection criteria ( Figure 1 ). Of these, 20 (69%) examined costs 13 , 17 , 20 – 26 , 29 37 , 39 , 40 and 19 (66%) examined prevalence 12 20 , 22 , 25 , 27 30 , 32 , 33 , 38 , 40 ; ten (34%) included both costs and prevalence. 13 , 17 , 20 , 22 , 25 , 29 , 30 , 32 , 33 , 40 Among the 29 studies, 17 (59%) examined diabetes; 16 (55%), mental disorders; 15 (52%), respiratory illnesses; 15 (52%), heart disease and stroke; 12 (41%), hypertension; 11 (38%), other chronic conditions; ten (34%), cancer; seven (24%), multiple chronic conditions; and six (21%), dyslipidemia.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations